Effects of training volume on strength and endurance in experienced resistance trained adults - Hass, C. J.; Garzaarella, L.; de Hoyos, D. V.; Pollock, M. L. (Medicine & Science in Sports & Exercise, 1998)
The effects of low volume strength training and high volume strength training on strength and endurance development in resistance trained adults (N = 40) were determined. Ss w ere assigned to a group of experimental training consisting of either one or three sets of 8-12 repetitions to failure, three times per week for 13 weeks. Performance gains were measured through 1RM for leg extension, leg curl, chest press, overhead press, and biceps curl. Muscular endurance was measured for chest press and leg extension as the number of repetitions to failure with a load of 75% of baseline 1RM. Both groups increased strength and muscular strength significantly with no difference between them on any measure. Implication: One strength training set to failure of 8-12 repetitions is as effective as three sets for improving strength and muscular endurance in the exercised muscles.